INNOVATIVE METHODS OF DEVELOPING VOCAL COMPETENCIES IN MUSIC EDUCATION (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2026)
This article analyzes innovative methods of developing vocal competencies in music education. It highlights modern pedagogical technologies, interactive methods, and digital tools.